Akuntabilitas Pengelolaan Dana Desa Tahun 2016 ( Studi Kasus : Desa Pemecutan Kaja, Kecamatan Denpasar Utara) - Kartika, Ayu (CITIZEN CHARTER, 2018)
ABSTRACT Accountability as an attitude of accountability in the management of village funds is a very important thing.The existence of transparent, responsible,effective, efficient, and economical attitude is the key to success from development and community empowerment based in accordance with Permenkeu 49/PMK.07/2016 on Procedures for Appropriation, Distribution,Use,Monitoring and Evaluation of Village Funds.This research uses descriptive qualitative method with data collection technique in depth interview to some informant . The theory used to dissect this problem is Financial Accountability Theory. Three indicators used in this study include: (a) Transparency indicator is evidenced by the absence of open village governance attitude towards village fund management from planning, implementation and accountability stages, (b) Indicators of Accountability is evidenced by the different amount of funds used in the village report on village financial accountability and report on the use of village funds owned by BPMPD Kota Denpasar due to budget changes in October and proven fictitious development included in the budget of APBDes,and (c) The principle of value of money is realized with the achievement of efficiency, effectiveness, and economics of village-managed programs. Keywords: Accountability, Transparency, Value of Money Principle